STORY- AND CHARACTER-MAKING SIGNIFICANCE OF THE TIME-SPACE IN THE POEM «TARASOVA NICH» BY TARAS SHEVCHENKO - Verlata, A. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article highlights timespace features of Taras Shevchenko’s poem about the heroic Ukrainian past of the impact in terms of time-space, including art space, on the plot concept of the author. Proved essential consideration in the light of the poem most skillful use of copyright chronotypical category as this view of the artist’s creative vision allows the imagination to compose a complete picture of a literary text .